1991
DOI: 10.1002/jmri.1880010306
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the central nervous system in divers

Abstract: A group of 70 professional divers and 47 healthy control subjects who had never dived were examined with magnetic resonance (MR) imaging to determine the prevalence of focal white matter changes in the brain. Spots of high signal intensity in white matter on proton density- and/or T2-weighted spin-echo images were detected in 42% of the control subjects and in 34% of the divers. In the control subjects, the prevalence of more than three changes was related to smoking, use of alcohol, head trauma, age of more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Since smoking habits were negatively related to excessive diving, it may be speculated that the diving group is comprised of either a highly selected group of healthier participants, or that divers are simply better trained so that they are better able to compensate for cognitive de®cits. This interpretation may correspond to the results obtained by Rinck et al (1991) whose control group showed more brain lesions than divers, poorer neuropsychological test performance, and a high association between brain lesions and life style variables. Selection mechanisms which favor divers, especially those with long diving exposure beyond the 50 msw level, may explain con¯icting results reported in the literature.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Since smoking habits were negatively related to excessive diving, it may be speculated that the diving group is comprised of either a highly selected group of healthier participants, or that divers are simply better trained so that they are better able to compensate for cognitive de®cits. This interpretation may correspond to the results obtained by Rinck et al (1991) whose control group showed more brain lesions than divers, poorer neuropsychological test performance, and a high association between brain lesions and life style variables. Selection mechanisms which favor divers, especially those with long diving exposure beyond the 50 msw level, may explain con¯icting results reported in the literature.…”
Section: Discussionsupporting
confidence: 63%
“…Partially in contrast to these straightforward results, Rinck et al (1991) studied 70 professional divers and 47 healthy controls without diving experience. Abnormal MRI changes were seen in 35% of the diving group and in 42% of controls.…”
Section: Introductionmentioning
confidence: 80%
“…However, although this prevalence was lower compared to that found in the divers, neither the number nor the size of lesions differed significantly between divers and controls. Todnem et al [5]and Rinck et al [25]reported significantly fewer lesions in commercial saturation divers (33 and 34%, respectively) than in their control subjects (43 and 42%, respectively). Since different imaging protocols were applied between groups, their comparability could be questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Most neuroimaging studies for detection of ischemic brain lesions have been performed in divers with acute decompression-related injuries of the central nervous system (2,3). However, as a recent study has shown (4), most divers may be neurologically asymptomatic despite an increased prevalence of brain lesions compared with nondiving controls.…”
mentioning
confidence: 99%